2008
DOI: 10.1111/j.1742-4658.2008.06743.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione transferases in bacteria

Abstract: Bacterial glutathione transferases (GSTs) are part of a superfamily of enzymes that play a key role in cellular detoxification. GSTs are widely distributed in prokaryotes and are grouped into several classes. Bacterial GSTs are implicated in a variety of distinct processes such as the biodegradation of xenobiotics, protection against chemical and oxidative stresses and antimicrobial drug resistance. In addition to their role in detoxification, bacterial GSTs are also involved in a variety of distinct metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
274
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 309 publications
(282 citation statements)
references
References 152 publications
(299 reference statements)
2
274
0
6
Order By: Relevance
“…Although Gst Pm -4 possesses no cysteine, it is able to conjugate the model substrates CDNB and GSH, which means it belongs to the GST superfamily [30,31]. Considering the fact that it is generally accepted that proteins with >40% sequence identity belong to the same class, Gst Pm -4 resembling a new branch GST (IsoJ) from Rhodococcus AD45 was confirmed that it belonged to a new class of GST [2].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Although Gst Pm -4 possesses no cysteine, it is able to conjugate the model substrates CDNB and GSH, which means it belongs to the GST superfamily [30,31]. Considering the fact that it is generally accepted that proteins with >40% sequence identity belong to the same class, Gst Pm -4 resembling a new branch GST (IsoJ) from Rhodococcus AD45 was confirmed that it belonged to a new class of GST [2].…”
Section: Discussionmentioning
confidence: 96%
“…The glutathione S-transferases (GSTs; EC 2.5.1.18) are a family of multifunctional proteins that can facilitate the nucleophilic attack of GSH to a large variety of reactive electrophilic endobiotic and xenobiotic [1,2]. GSTs are widely distributed in natural organisms and are found in both eukaryotes and prokaryotes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, GST participates in protecting cells against the damage of oxidative stress (43,44), and Ysr29 repression of GST levels may prevent an aberrant response to this stress. In addition, OmpA is an outer membrane protein known to play a role in the pathogenesis of E. coli K1 and acts as an adhesin, invasin, and immune evasin (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%